Assessment of Evapotranspiration Models for the Humid Tropical Region of Tavanur - PRAVALIKA Y.R; Dr. Asha Joseph (Guide) (Tavanur 2017 Department of Irrigation and Drainage Engineering)
Assessment of Evapotranspiration Models for the Humid Tropical Region of Tavanur
Assessment of Evapotranspiration Models for the Humid Tropical Region of Tavanur